ANALISIS HUKUM TERHADAP PELANGGARAN KODE ETIK HAKIM AKIBAT TIDAK NETRAL DALAM PROSES PERSIDANGAN - Fadli Winata; Muhammad Suwandi; Faturrohman Faturrohman (QAIMUDDIN: Journal of Constitutional Law Review, 2023)
A judge is a person who carries out judicial duties or powers as regulated in law. In carrying out one's duties and authority as a judge, of course there are rules when becoming a judge, including those regarding the Code of Ethics and Code of Conduct for Judges. A judge is expected to adhere to high ethical standards to ensure integrity, independence, and fairness in the justice system. Unethical behavior by showing a non-neutral attitude in the trial process can damage public confidence in justice and tarnish the reputation of the justice system. The aim of this research is to look at these violations in terms of the Judge's Code of Ethics. This research method is qualitative research with the type of library research and analysis using a normative and sociological approach. The result of this research is that there is non-neutral behavior carried out by judges in the trial process with the aim of taking sides which clearly violates the Judge's Code of Ethics. The results of this research provide an in-depth picture of the various disciplinary actions that may be taken against judges, ranging from warnings and administrative sanctions to further legal action.